Facebooking ethnicity in the political storytelling of Nigerians (2016)
After the so-called “Arab Spring”, the capacity of social networking sites to change communicative spaces and political landscapes has been studied with increased attention. The #OccupyNigeria Protests and #BringBackOurGirls campaigns manifested the influence of social media on civic engagement of Nigerians. On the other hand, Nigeria as an ethnic fault line state has experienced political tensions of brutish magnitude that have hindered nation building as well. However there is paucity of scholarly investigations that peer into the influence of social media mediated political storytelling in enhancing ethnic stereotypes or galvanizing ethnic cohesion within the context of nation building. This paper investigated the influence of ethnicity on political storytelling of Nigerians on Facebook. This study employed survey by administering online open-ended questionnaires to respondents. Data suggests that respondents' political storytelling was not affected by the ethnicity of their Facebook friends. Findings also showed that the political storytelling of their friends on Facebook was laden with ethnocentrism and that Facebook mediated political storytelling promotes ethnic stereotypes. The findings were discussed based on the meso- storytelling proposition of the Communication Infrastructure Theory, notions of nation building in the African context and reviewed literature on social media.